Mentors and teachers: testing the effectiveness of simultaneous roles on school performance from a basic psychological needs satisfaction perspective - Simões, F.; Alarcão, M. (Instructional Science, 2014)
The mentor’s background in educational roles has been presented as a moderator of School-Based Mentoring (SBM). However, the analysis of overlapping mentoring and teaching roles has been underemphasized in the literature. The aim of this study is to test whether the combination of mentoring and teaching roles influences the mentees’ school performance, within a Portuguese SBM program. A three-stage experimental study was conducted in order to compare mentored (n = 157) and non-mentored students (n = 160) enrolled in formal basic education (5th to 8th grades). Multivariate Analyses of Covariance (MANCOVA) revealed that the combination of mentoring and teaching roles was effective in reducing the mentees’ unexcused absences and in improving their grades in Portuguese language and math as well as their Grade Point Average (GPA) compared to equivalent non-mentored students. Further analyses demonstrated that an increased satisfaction of the mentored students Basic Psychological Needs (BPN) promoted better school performance outcomes when compared with non-mentored students with an identical perception of BPN support. However, mentored students that experienced an increased satisfaction of BPN had marginally significantly worse Grade Point Average (GPA) than the mentored students that perceived less or similar BPN support within SBM. These mixed trends are discussed and recommendations are made for a more balanced support of BPN in SBM relationships and across the different relationships held between the mentees and other teachers, in order to foster an improvement of school performance.